“Menyusui asi-q” android application for relax and smooth breastfeeding - Kharisma Virgian; Desy Setiawati Setiawati (Science Midwifery, 2023)
Breastfeeding is an instinct of a mother, however, it must be supported by internal factors and good external. The success of the breastfeeding process can be supported by knowledge, good social support, calmness, and comfort of the mother when breastfeeding. One form of support as an educational and relaxation medium developed for breastfeeding mothers is the android-based "Menyusui ASI-Q" application. The purpose of this study was to determine the influence of the application on the knowledge, anxiety of the mother, and the smoothness of the breastfeeding process. The respondents to this study were 35 breastfeeding mothers from independent midwives in Palembang. The quasi-experiment research method uses one-group pre-test and post-test design approaches. Statistical tests using the Mc Nemmar test, the results found that there were significant differences in knowledge, anxiety, and smoothness of the breastfeeding process before and after using the application (ρ = 0.000). Educational media for breastfeeding mothers can increase maternal knowledge and the breastfeeding process becomes calmer and smoother.